Prevalence of Mental Disorders and Impact on Quality of Life in Patients With Pulmonary Arterial Hypertension - Olsson, Karen M.; Meltendorf, Tanja; Fuge, Jan; Kamp, Jan C.; Park, Da-Hee; Richter, Manuel J.; Gall, Henning; Ghofrani, Hossein A.; Ferrari, Pisana; Schmiedel, Ralf; Kulla, Hans-Dieter; Heitland, Ivo; et al. (Frontiers in Psychiatry, 2021)
Objective: Mental health may affect the quality of life (QoL) in patients with pulmonary arterial hypertension (PAH). However, mental disorders have not been systematically assessed in these patients. We examined the prevalence of mental disorders using structured interviews and determined their impact on QoL in patients with PAH. Methods: This study included 217 patients with PAH from two German referral centers. Psychiatric disorders were assessed using the structured clinical interview for DSM-V. QoL was assessed using the WHO Quality of Life questionnaire (short form). The diagnostic value of the Hospital Anxiety and Depression Scale was evaluated by receiver operating characteristic curve analysis. Results: More than one third of the patients had psychological disorders with current or past adjustment disorder (38.2%), current major depressive disorder (23.0%), and panic disorder (15.2%) being the most prevalent mental illnesses. About half of the patients with a history of adjustment disorder developed at least one other mental illness. The presence of mental disorders had a profound impact on QoL. The Hospital Anxiety and Depression Scale ruled out panic disorder and depression disorder with negative predictive values of almost 90%. Conclusion: Mental disorders, in particular adjustment disorder, major depression, and panic disorder, are common in patients with PAH and contribute to impaired QoL in these patients. The Hospital Anxiety and Depression Scale may be used as a screening tool for the most common mental health disorders. Future studies need to address interventional strategies targeting mental disorders in patients with PAH.